The potency of a single drug to manage Udavart in infant: A case report - Kahdoliya, Dharmisha; Patel, Bhupesh; Kapadiya, Manisha; Bholane, Avinash (Journal of Ayurveda Campus, 2024)
Background: Udavart (reverse movement of Vata) is among the most common Vata diseases, astonishingly most underrated, and misunderstood clinical conditions. Materials and methods: A 49-day-old infant was diagnosed with Udavart. The case was managed by a single drug. Haritaki (Terminalia chebula Retz.) fruit rubbed with mother’s milk and given to the child. Haritaki Churna (powder of Terminalia chebula Retz.) was also given to the mother with Pathya Palana (does and don’ts) for seven days. Results and Discussion: After 7 days of treatment for the child and mother, grunting ceased completely and the child got a sound sleep. Conclusion: Haritaki has Deepen (appetiser), Pachan (digestion), and Vatanulomaka (carminative) properties. It was found that Haritaki gives excellent results in Udavart.